A new ferroelastic hybrid material with a large spontaneous strain: (Me3NOH)2[ZnCl4]. Issue 61 (10th July 2019) - Yuan, Wei; Zeng, Ying; Tan, Ya-Yin; Zhou, Jian-Hua; Xu, Wei-Jian; Zhang, Wei-Xiong; Chen, Xiao-Ming
Abstract : A new organic–inorganic hybrid undergoes a ferroelastic phase transition at 351 K accompanied with a large spontaneous stain. Abstract : A new hybrid compound (Me3 NOH)2 [ZnCl4 ] undergoes an above-room-temperature mmmF 2/ m ferroelastic phase transition and exhibits a large spontaneous strain of 0.129, owing to an order–disorder transition of organic cations.